Reconsidering the Nature of the Unconscious: A Question on Psychoanalysis in Literary Studies - Suharjanto, SJ, L. (LLT Journal: A Journal on Language and Language Teaching, 2012)
Psychoanalysis has been used invariably in literary studies, as it helps literary interpretation to touch the often-puzzling-dimension of motives and feelings in literary works. The domination of psychoanalysis in the twentieth century, however, has been questioned with the new awareness that the unconscious mind is not innate but constructed. Such a disposition challenges not only the practice of using psychoanalysis in literary studies but also the validity of psychoanalysis itself.